CARING FOR THE ENVIRONMENT WITH A SOCIAL SPIRIT THROUGH THE WASTE BANK UNIT PROGRAM - Marlina, Asti; Zaidan Sinaga, Hanif; Pramono, Setio; Ariyo Bimo, Widhi; Sinta Tiara, Euis; Rusydiana MS, Rizqy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Waste management is a serious challenge that occurs in several countries. Poor waste management will lead to several problems. One movement that can overcome waste management is the establishment of waste banks. As one of the innovative steps that can overcome waste management problems in a sustainable manner. Waste banks are institutions that provide economic incentives for communities to recycle and utilize waste effectively. Community service activities in Nagrak village saw this phenomenon and made this a mainstay program. It is expected to provide in-depth insight into the contribution of waste banks in managing waste and achieving sustainable development goals. The results of this community service are expected to provide a basis for policy makers, industry players and the general public to improve the implementation and effectiveness of waste banks as an innovative solution in waste management and environmental sustainability.